Influence of preheating on chatter and machinability of titanium alloy - Ti6A14V - Kamdani, Kamaruddin (2005)
Numerous studies on machinability of titanium and its alloys have been conducted in the past few decades with the main objective of reducing cost of machining especially of aerospace alloys. Though classified as "difficult-to-cut" materials, titanium and its alloys are attractive materials due to their unique high strength-weight ratio, which is maintained up to elevated temperatures and their exceptional corrosion resistance. In this work, an experimental investigation of the influence of workpiece preheating using induction heating has been conducted for improvements of machinability of titanium alloy Ti-6A1-4V ASTM B348. The inserts used were uncoated cemented carbide filled into a 16 mm diameter end mill tool. The cutting speeds used in these experiments were 40, 80, 120 and 160 m/min; the depths of cut were 1 and 1.5 mm and the feed rates were 0.1 and 0.15 mm/rev. Thermo-couples were used in measuring the surface temperature of work material during machining. The experiments of end milling operation conducted on Vertical Machining Center (VMC) were designed to look into the effect of preheating on chip serration and chatter, cutting force and torque, tool wear and surface finish. A comparison of the above criteria for room temperature and preheated machining was made. The results show that preheating machining improves the machinability of titanium alloy. Increased plasticity of the work material during preheating reduces the frictional forces on the tool face and the fluctuation of cutting force and also contributes to improved damping capacity of the system. As a result preheated machining results in reduction in vibration amplitudes at resonance frequencies up to 67%. An increase in cutting force and torque mean value leads to the formation of relatively thicker chips, which in turn leads to an increase in chip-tool contact length. The hottest spot on the tool is thus shifted away from the cutting edge leading to a more favourable temperature distribution in the tool. More stable cutting, longer chip-tool contact length and favourable temperature distribution in the tool helps in reducing the dynamic stresses acting on the tool. This in turn reduces the enhances of micro and macro chipping of the tool. This leads to uniform and much lower tool wear up to three times reduction in flank wear has been achieved. Lower tools wear, helps in maintaining a sharp cutting edge at the nose section and the flank areas of the tool resulting in smoother surface roughness values during preheated machining.